Teachers as informants: countering extremism and promoting violence - Faure-Walker, Rob (Journal of beliefs and values, 2019)
This article is a response to Muslim students reporting that they had been silenced by fear of the PREVENT Counter-Terrorism Strategy. By adopting a Critical Realist stance, real generative mechanisms of this actual phenomenon are investigated and theorised. Recognition of changing definitions of both 'radicalisation' and 'extremism' in different versions of PREVENT results in the discursive aspect of these real generative mechanisms being investigated using critical discourse analysis (CDA). This analysis identifies the emergence of a violent discourse of 'radicalisation' and 'extremism' (RadEx) that it is theorised has the capacity to promote rather than prevent violence. Finally, a process by which this production of violence in the classroom might have been avoided is explored and this indicates that critique of government efforts to counter 'radicalisation' and 'extremism' is a vital aspect of pedagogy in the context of PREVENT and the War on Terror.